Metrics of sequence constraint overlook regulatory sequences in an exhaustive analysis at phox2b - McGaughey, David M.; Vinton, Ryan M.; Huynh, Jimmy; Al-Saif, Amr; Beer, Michael A.; McCallion, Andrew S. (Genome Research, 2008)
Despite its recognized utility, the extent to which evolutionary sequence conservation-based approaches may systematically overlook functional noncoding sequences remains unclear. We have tiled across sequence encompassing the zebrafish phox2b gene, ultimately evaluating 48 amplicons corresponding to all noncoding sequences therein for enhancer activity in zebrafish. Post hoc analyses of this interval utilizing five commonly used measures of evolutionary constraint (AVID, MLAGAN, SLAGAN, phastCons, WebMCS) demonstrate that each systematically overlooks regulatory sequences. These established algorithms detected only 29%–61% of our identified regulatory elements, consistent with the suggestion that many regulatory sequences may not be readily detected by metrics of sequence constraint. However, we were able to discriminate functional from nonfunctional sequences based upon GC composition and identified position weight matrices (PWM), demonstrating that, in at least one case, deleting sequences containing a subset of these PWMs from one identified regulatory element abrogated its regulatory function. Collectively, these data demonstrate that the noncoding functional component of vertebrate genomes may far exceed estimates predicated on evolutionary constraint.
10.1101/gr.6929408